2017
DOI: 10.4088/jcp.16m10976
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Antipsychotic Use and Major Cardiovascular Events

Abstract: Older adult patients under antipsychotic regimens with high or intermediate risk of metabolic side effects may face a higher incidence of major cardiovascular events than those under a low-risk regimen during long-term follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 0 publications
0
14
0
1
Order By: Relevance
“…Many APDs currently available in the United States have been associated with metabolic side effects to varying degrees (Kendall, 2011 ). Clozapine and olanzapine, though the most clinically effective APDs available, have also shown the greatest risk for inducing IR and significantly elevate risks for major cardiovascular events (e.g., acute coronary syndrome, ischemic stroke, and peripheral artery disease) by up to 2.8-fold (Szmulewicz et al, 2017 ). Indeed, 32% of patients taking olanzapine develop IR, in addition to gaining at least 15% of their baseline bodyweight (Citrome et al, 2011 ).…”
Section: Contribution Of Antipsychotic Medications To Metabolic Riskmentioning
confidence: 99%
“…Many APDs currently available in the United States have been associated with metabolic side effects to varying degrees (Kendall, 2011 ). Clozapine and olanzapine, though the most clinically effective APDs available, have also shown the greatest risk for inducing IR and significantly elevate risks for major cardiovascular events (e.g., acute coronary syndrome, ischemic stroke, and peripheral artery disease) by up to 2.8-fold (Szmulewicz et al, 2017 ). Indeed, 32% of patients taking olanzapine develop IR, in addition to gaining at least 15% of their baseline bodyweight (Citrome et al, 2011 ).…”
Section: Contribution Of Antipsychotic Medications To Metabolic Riskmentioning
confidence: 99%
“…Although the results of lithium reducing the risk of stroke in BD patients remains conflicting, 37,38 it is well known that older adult patients under antipsychotic regimens may face an increasing incidence of major cardiovascular events during long-term follow-up. 39 The duration of either antipsychotic or lithium treatment is comparable in these two group. Therefore, our data could not find the effect of psychotropic agents on the risk of stroke.…”
Section: Discussionmentioning
confidence: 85%
“…Parameters for treatment including age at the last psychiatric visit, age at the first and the last acute psychiatric admissions, number of lifetime acute psychiatric admissions, and duration of antipsychotics and lithium treatment were not significantly different between these two groups. Although the results of lithium reducing the risk of stroke in BD patients remains conflicting, it is well known that older adult patients under antipsychotic regimens may face an increasing incidence of major cardiovascular events during long‐term follow‐up . The duration of either antipsychotic or lithium treatment is comparable in these two group.…”
Section: Discussionmentioning
confidence: 99%
“…Poorer secondary prevention has been shown previously in ischemic heart disease (16), and a study from the US reported that the Framingham 10-year risk of coronary heart disease was increased by 79% in patients with schizophrenia (9). One potential driver of poorer cardiovascular health in these patients could be the cardiovascular side effects of antipsychotic drugs (13, 22).…”
Section: Discussionmentioning
confidence: 99%
“…Circulatory disease is one of the major causes of excess death in people with psychiatric disorders, second to suicide (10, 11). This may be due to several factors, including lifestyle, poor identification and management of risk factors and the disease itself, lack of health literacy, and side effects of antipsychotic medication (8, 12), which may further increase the risk of cardiovascular events (13).…”
Section: Introductionmentioning
confidence: 99%